Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.2754/avb201382030297
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mixed use of thyme and fennel oils on biochemical properties and electrolytes in rainbow trout as a response to Yersinia ruckeri infection

Abstract: The aim of study was to compare the effects of supplementation of food with herbal oils (Thymus vulgaris and Foeniculum vulgare) on biochemical properties and electrolytes of rainbow trout infected with Yersinia ruckeri. In total, 120 healthy fish (mean weight 84 ± 1.02 g) were equally divided into four experimental groups. The experimental study was carried out for one week. The first group was control without supplementation and infection, the second group was infected and without oil supplementation, the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 20 publications
4
21
0
Order By: Relevance
“…Diet supplementation with herb oils (Thymus vulgaris and Foeniculum vulgare) can increase disease resistance. Thyme and fennel oils can improve the immune system against Yersinia ruckeri infection by increasing some biochemical indices and electrolytes in rainbow trout (Kucukgul Gulec et al 2013). Similar immunological results have been shown in broiler chickens supplemented with F. angulata extract (Govahi et al 2013;Rostami et al 2015).…”
Section: Discussionsupporting
confidence: 67%
“…Diet supplementation with herb oils (Thymus vulgaris and Foeniculum vulgare) can increase disease resistance. Thyme and fennel oils can improve the immune system against Yersinia ruckeri infection by increasing some biochemical indices and electrolytes in rainbow trout (Kucukgul Gulec et al 2013). Similar immunological results have been shown in broiler chickens supplemented with F. angulata extract (Govahi et al 2013;Rostami et al 2015).…”
Section: Discussionsupporting
confidence: 67%
“…However, the highest resistance (31.58% vz 4.76% in control fish) was seen in fish fed 0.5 ml/kg feed. Supplementation of thyme oils at 10 ml herbal essential oils (mixed thyme and fennel)/100 g feed for 21 days could improve resistance of rainbow trout against Yersinia ruckeri infection by increasing levels of some immunity factors (Gulec et al (). Gültepe et al () also showed that tilapia fed 1% thyme exhibited 78% survival compared to 39% in control fish after fish being challenged with Streptococcus iniae .…”
Section: Discussionmentioning
confidence: 99%
“…Thymus vulgaris has been widely distributed in Iran, and has long been used as herb especially in traditional medicine. Application of Thyme essential oils as dietary supplement has been demonstrated in some fish species including rainbow trout (Onchorhyuncus mykiss) (Kucukgul Gulec et al, 2013), common carp (Cyprinus carpio) (ALsafah & AL-Faragi, 2017) and gibel carp (Carassius gibelio) (Zadmajid & Mohammadi, 2017), but there is no available information about Thyme oils on immune related gene expression in rainbow trout (O. mykiss). The present work aimed to investigate the dietary administration of Thyme oils on growth performance, immune-related gene expression and disease resistance of rainbow trout juvenile.…”
mentioning
confidence: 99%
“…They found reduced blood total cholesterol. Gulec et al (2013) noted significantly higher (P<0.05) contents of total protein, albumin, cholesterol, triglycerides, bilirubin, K, Na, Ca and Mg after addition of plant oils (Thymus vulgaris and Foeniculum vulgare) compared to the control. Present findings are not in agreement with those presented by Levkut et al (2011) who observed that chickens fed oregano oil supplemented diet had significantly higher serum magnesium concentration and slightly lower serum phosphorus level in comparison with birds from control group.…”
Section: Blood Parameters Of Laying Hensmentioning
confidence: 99%
“…However, the sensory quality of eggs isn´t often affects (Garcia-Rebollar et al, 2008). The addition plant oils have positive effect on contents of total protein, albumin, cholesterol, triglycerides (TG), bilirubin, K, Na, Ca and Mg in blood serum (Gulec et al 2013). Flaxseed is emerging as one of the key sources of phytochemicals in the functional food area.…”
Section: Introductionmentioning
confidence: 99%